Nanozyme Applications: A Glimpse of Insight in Food Safety - Wu, Long; Zhou, Shuhong; Wang, Gonglei; Yun, Yonghuan; Liu, Guozhen; Zhang, Weimin (Frontiers in Bioengineering and Biotechnology, 2021)
Nanozymes own striking merits, including high enzyme-mimicking activity, good stability, and low cost. Due to the powerful and distinguished functions, nanozymes exhibit widespread applications in the field of biosensing and immunoassay, attracting researchers in various fields to design and engineer nanozymes. Recently, nanozymes have been innovatively used to bridge nanotechnology with analytical techniques to achieve the high sensitivity, specificity, and reproducibility. However, the applications of nanozymes in food applications are seldom reviewed. In this review, we summarize several typical nanozymes and provide a comprehensive description of the history, principles, designs, and applications of nanozyme-based analytical techniques in food contaminants detection. Based on engineering and modification of nanozymes, the food contaminants are classified and then discussed in detail via discriminating the roles of nanozymes in various analytical methods, including fluorescence, colorimetric and electrochemical assay, surface-enhanced Raman scattering, magnetic relaxing sensing, and electrochemiluminescence. Further, representative examples of nanozymes-based methods are highlighted for contaminants analysis and inhibition. Finally, the current challenges and prospects of nanozymes are discussed.